Tantangan Guru Pai Dalam Menghadapi Era Perubahan Globalisasi Teknologi Industri 4.0 di SMA Negeri 01 Bengkulu Tengah - Sari , Renda Ratna; Febrini, Deni; Walid, Ahmad (Yayasan Darusssalam Bengkulu, 2021)
This study aims to describe the challenges of Islamic Religious Education teachers in facing the changes in the era of globalization of the technology industry 4.0 at SMA Negeri 01 Bengkulu Tengah. The research method used is descriptive qualitative and refers to case studies. Data collection was carried out by observation, interviews and documentation. For data validity using observation persistence, triangulation techniques and sources.The results of the study show that the challenges faced by Islamic Education teachers in the changing era of globalization of the technology industry 4.0 in SMA Negeri 01 Bengkulu Tengah, there are several challenges, one of which is that teachers must be required to be digital literate where teachers must increase their understanding and knowledge in technology in order to implement this knowledge. In the teaching process, another challenge faced by Islamic Education teachers is that teachers must be able to innovate their teaching methods according to existing developments. Apart from teachers, other challenges came from students, where students' morale was eroded due to changes in technological globalization, and student social action towards their environment was also eroded, not only among students but also appearing indifferent to their responsibilities as students.